Traditional Market Development Strategy as a Shopping Tourism Attraction in West Lombok Regency, West Nusa Tenggara: Case Study of Tenten Golong Traditional Market - Widiantara, I Gusti Agung Bagus; Wirya, I Made Suwitra; Dwi Putranto, Isa Wahyoedi (Akademi Komunitas MAPINDO, 2023)
Markets play an important role in the economy of a rural community. The market not only functions as ameeting place for sellers and buyers to carry out transactions, but also increases its function as a center forvarious community activities ranging from selling artistic, agricultural, handicraft, culinary, cultural, religiousproducts with the existence of the Melanting Temple for Hindus, especially those earn their living as traders inthe market. So it is very appropriate for the market to be called the center of the economy and also a touristattraction, especially shopping tourism. The existence of this market, some of which are global, some aredeveloping on a regional scale or traditional markets are found in every village in Indonesia, including onLombok Island, West Nusa Tenggara Province. In 2023, West Nusa Tenggara Province targets 2 million touriststo visit and spend their free time and money on holidays, whether they come in groups or independently. Forthe arrival of tourists, it is necessary to provide adequate tourist accommodation and tourist attractions, interms of quality and quantity. One of the tourist attractions offered to tourists visiting West Nusa TenggaraProvince is the Tenten Traditional Market with its various unique potentials which is not yet widely known andthere is a need for a development strategy in this qualitative descriptive research which is analyzed using SWOTAnalysis. With this SWOT analysis, the strengths, weaknesses, opportunities and threats that occur inconnection with the existence of the Tenten Golong Traditional Market as a tourist attraction in West NusaTenggara Regency are known. After knowing the elements of this SWOT, it is concluded that the TentenTraditional Market has the potential to be developed into a shopping tourist attraction by implementing severalgood strategies to improve the internal environmental conditions of the market, the quality of human resourcesmanaging the market, product quality, marketing and the external environment in outside that market.Keywords: Traditional Market, Development Strategy, SWOT Analysis